Chemical Looping Co-Gasification Characteristics of Cyanobacterial/Coal Blends - Tianxu Shen; Jiang Zhang; Laihong Shen; Lei Bai; Jingchun Yan (Energies, 2020)
The frequent outbreak of cyanobacteria bloom results in an urgent need for the resource utilization of cyanobacteria. However, the development of routine thermal treatment (i.e., gasification and pyrolysis) is hindered by the issue of high moisture content. In order to minimize the dewatering requirement, this study investigated the chemical looping co-gasification of the cyanobacteria/coal mixture. The results showed that the residual moisture of cyanobacteria not only could serve as the gasifying agent of coal, but also presented a better gasification effect than the injecting steam. Meanwhile, blending cyanobacteria also improved the performance of coal chemical looping gasification in terms of the syngas quality, gasification rate, and carbon conversion efficiency. Cyanobacteria pyrolysis supplied abundant hydrocarbons and hydrogen-rich gases. The highest syngas yield of 1.26 Nm3/kg was obtained in the mixture fuel of 46 wt.% cyanobacteria and 54 wt.% coal under a 0.3 oxygen carrier-to-fuel ratio. A slight interaction effect was observed in the pyrolysis process, in which the reactivity of coal pyrolysis was enhanced by the oxygenated groups of cyanobacteria volatile. The dominant motive of the interaction effect was the catalytic effect of alkali metals of cyanobacteria ash on the coal gasification. However, the formation of aluminosilicates deactivated alkali metals and further inhibited the char gasification. The intensity of interaction effect was demonstrated to be highly relevant with the (Na + K)/Al molar ratio of ash. The most prominent interaction effect occurred for the sample with 82 wt.% cyanobacteria, but a negative interaction was observed in the sample with 10 wt.% cyanobacteria. Both homogeneous reaction and shrinking core models showed the excellent fitting performance in the char gasification process. However, these two models could not be applied to the initial pyrolysis process because of the intricate mechanisms.